ADSORPSI ION LOGAM Pb2+ DAN Cu2+ OLEH BENTONIT TERAKTIVASI BASA (NaOH) - Indah Kumala Dewi, Putu Aprilliana; Suarya, Putu; Sibarani, James (Jurnal Kimia (Journal of Chemistry); Vol. 9, No. 2 Juli 2015DO - 10.24843/JCHEM.2015.v09.i02.p14, 2015)
The aim of this study is to determine the adsorption capacity of NaoH activated bentonites in reducing metal ions Pb 2+ and Cu 2+ from their solutions. The characterization of the activated bentonites was carried out by determining the specific surface area using methylene blue adsorption method, the numbers of the active site by acid-base titration, and determining the basal spacing using X-ray diffraction (XRD). Adsorption parameters such as contact time, pH, and the isotherm adsorption curves were determined by atomic absorption spectrophotometer (AAS). The specific surface area and the number of active sites of the NaOH-activated Bentonite were 22.1017 m 2 /g and 32.8716 x 10 20 atoms/g respectively. This vakue was higher than non-activated ones which were 12.6602 m 2 /g and 31.5847 x 10 20 atoms/g respectively. The optimum condition of Pb 2+ adsorption on activated bentonite was obtained at pH 3 with contact time under 5 minutes following the Langmuir isoterm pattern while the optimum condition of Cu 2+ adsorption was obtained at pH 4 with contact time under 5 minutes following the Langmuir isoterm adsorption suggesting that the adsorption took place by chemical adsorption. The adsorption capacities of Pb 2+ and Cu 2+ were 185.50 mg/g and 30.00 mg/g respectively.
Keywords: NaOH-activated Bentonite, Capacity of Adsorption, Metal Ion Cu2+, Metal Ion Pb2+